Risk Assessment of Vitamin B12 Deficiency in Male Population of Bahawalpur District - Muhammad Wasim Tasleem; Sehrish Rana Rajpoot; Muhammad Irfan; Muhammad Irfan; Muhammad Imran; Muhammad Asad; Mehboob Ahmad; Farah Zafar (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
The primary goal of this study was to investigate the prevalence of vitamin B12 insufficiency in various age groups. It is descriptive cross-sectional research in which 180 individuals were assessed for vitamin B12 from the district of Bahawalpur. Patients were placed into groups based on their ages. BMI and serum B12 levels were analyzed and a questionnaire was filled out by them. Data were statistically analyzed through T-test, ANOVA followed by post-hoc Dunnette T3 test, and frequency by Chi-square test. Results revealed that Vitamin B12 statically differed in groups of marital status, sun exposure/day/hour, diet groups, diabetic groups, and age groups. While BMI differed according to different weight groups, sun exposure/day/hour, diabetic groups. The frequency of all the groups statistically differed in all the groups. BMI had a negative correlation with the Vitamin B12 level. It was concluded that the male population was not at risk but the old population at the risk of low levels of vitamin B12.